Policy Analysis PT. BPRS Berkah Ramadhan In Providing Multi-Purpose Financing To MSME Customers In The Covid-19 Pandemic - Tarmizi, Rasyid; Sunardi, Sunardi; Aulia, Nursyifa; Hananto, Djoko (UNIVERSITAS RAHARJA, 2023)
This study aims to determine the policies implemented by BPRS Berkah Ramadhan in providing multipurpose financing to MSME customers during the COVID-19 pandemic. The research method used is a qualitative method with the type of case study research. The informants selected in this study were the head of the marketing department, expert informants and customers of micro, small and medium enterprises. The results showed that the BPRS Blessings of Ramadan Policy during the covid-19 pandemic in providing multipurpose financing to micro, small and medium business customers, namely (1) Customers who experience problematic financing, the bank will provide policies in the form of relief in paying installments, providing restructuring and relaxation financing by using rescheduling to MSME customers whose businesses have been affected by COVID-19 as evidenced by the customer's business income report. (2) the customer has good collectibility in applying for financing, the business must run for at least 1 year. The procedure carried out by BPRS Berkah Ramadhan in analyzing the provision of financing to micro, small and medium business customers is to conduct surveys to business locations and collect business financial statements. After that, if it has been approved by the leadership, the bank will issue an SP3 or a letter of approval for a financing application to the customer, if it is approved by both parties, a financing contract will be made and the financing can be disbursed